Mitigation of the potential fraud in the era of business digitalization in the covid 19 pandemic: exploration of accountant’s role and challenges - Nurcahya, Yulida Army (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to see the role of accountants in mitigating the potential for fraud that occurs in the digital business era during the Covid-19 pandemic through the implementation of forensic accounting. This research will use a qualitative approach by using various previous studies and studies as the data source. This study found that business accountants have an essential role in the Covid-19 pandemic. Business accountants can have a crucial role in the digital information industry in controlling internal problems so that the results are efficient and effective, thereby reducing the risk of fraud. Forensic accounting can help detect the potential for fraud to mitigate the consequences of fraud in this digital era. If corruption has occurred, then what the Forensic Accountant must do is detect corruption. Forensic Accountants can detect fraud and corruption problems more quickly because Forensic Accountants already know and master the techniques in detecting fraud and corruption.